Dynamics of trunk type robot with spherical piezoelectric actuators - Augustaitis, Aistis; Jurėnas, Vytautas (IAES International Journal of Robotics and Automation (IJRA), 2020)
Trunk type robots (TTRs) are exclusive. These robots can provide a high level of maneuverability and have a potential in medicine or high risk zones. TTRs are determined as a long serial linkage of similar segments. They are usually connected using tendons or small actuators. A spherical actuator is the most appreciable option. The motion of real spherical actuator (RSA) can be easily obtained applying an inverse piezoelectric effect. It has three independent spinning axes. These axes are perpendicular to each other despite the history of excitation. Kinematics and dynamics of RSA almost have no basics regardless of mentioned features. This situation can be explained according to common disadvantages of other SAs: sophisticated structure and complex control. The structures and abilities of TTRs are reviewed in the first section of this article. At the beginning of the fourth section the kinematics of piezoelectric TTR with two different RSAs is introduced. Its results of inverse dynamics using Euler-Lagrange equations are presented at the end of the fourth section. Similar results are derived using an analytical-potential method in the fifth section. It is quite accurate and effective option to determine inverse dynamics of the TTR employing an analytical-potential method.